High Performance Liquid Chromatography Based on Computational Study for the Determination of Etilefrine Hydrochloride in the Presence of its Oxidative Degradation Product. Issue 4 (3rd July 2016) - Attia, Khalid A.M.; El-Abasawy, Nasr M.; El-Olemy, Ahmed; Abdel-Raoof, Ahmed M.
Abstract: A simple, sensitive, specific and accurate stability indicating HPLC method was developed for the determination of etilefrine hydrochloride (ETF) in presence of its oxidative degradate. Computational and theoretical studies were done electronically and geometrically to investigate the affinity of ETF and its oxidative degradate to the stationary phase. The analysis was carried out on an ODS SUPELCO C18 (25 cm X 4.6 mm, 5 μm particle size) using a mobile phase consisting of [0.1M phosphate buffer, pH 4: acetonitrile (30:70, v/v)]. The analysis was performed at ambient temperature with a flow rate of 1 mL/min and UV detection at 220 nm. The proposed method can selectively analyzes the drug in presence of up to 80% of its oxidative degradate with mean recovery ± RSD % of 99.54±0.503. The proposed method was extensively validated according to the ICH guidelines and used for estimation of ETF in tablets and the obtained results were statistically compared with those of the reported method by applying t-test and F-test at 95% confidence level and no significant difference was observed regarding accuracy and precision.